Eating habits and nutritional status according to Body Mass Index in university students – 2023 - Junchaya Yllescas , Vilma Amparo (2024)
Objective: To determine the relationship between eating habits and nutritional status according to Body Mass Index (BMI) in university students. Material and Methods: This study follows a cross-sectional, descriptive, prospective and non-experimental correlational design. The survey technique was used with a reliability of 0.848 with Cronbach's alpha, to measure eating habits using a probability sample of 372 students from different semesters of the Faculty of Pharmacy and Biochemistry by means of an adapted questionnaire. Observational methods and anthropometric measurements were used to evaluate the nutritional status of the students. Results: 79 % were women and 76.1 % were single, of which 26.9 % were from Huancayo, followed by 12.6 % from Huancavelica. Regarding place of birth, 27.7 % were born in Huancayo, followed by 13.4 % in Huancavelica, 59.1 % of them work and study; 48.4 % have a body mass index within normal limits, 31.7 % are overweight and 12.6 % obese. When describing their eating habits, 68.5% choose to cook their meals, 62.6% eat fruit and/or juice between meals and 75.5% eat rice with beans and/or chickpeas or peas, 76.4% of the population chooses to eat breakfast at home, 43.5% of the population drinks bottled soft drinks at dinner, 50.3% eat occasionally between meals, 42.2% drink a small amount of liquid, an average of 500 ml per 1 liter, and 54% of university students have regular eating habits, 50.3% eat occasionally between meals, 42.2% drink a small amount of liquid, an average of 500 ml per 1 liter and 54% of university students have a regular eating habits, while 18% are bad. Conclusions: The statistical correlation between eating habits and IMC nutritional status in university students is low.